2019
DOI: 10.2166/wst.2019.214
|View full text |Cite
|
Sign up to set email alerts
|

An electrode-assisted anaerobic digestion process for the production of high-quality biogas

Abstract: Biogas is a sustainable, renewable energy source generated from organic waste degradation during anaerobic digestion (AD). AD is applied for treating different types of wastewater, mostly containing high organic load. However, AD practice is still limited due to the low quality of the produced biogas. Upgrading biogas to natural gas quality (>90% CH4) is essential for broad applications. Here, an innovative bio-electrochemically assisted AD process was developed, combining wastewater treatment and bioga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…There was a significant increase in the yield of biogas with treatment, possibly due to the specific effect of the electric current on complexly degradable quail manure. These findings are supported by previous studies conducted on substrates such as agroindustrial wastewater [28], municipal sewage sludge [29,30], and liquid waste from the wine industry [25,31]. On the sixth day of treatment, the CO 2 yield increased (24.0% in the conventional conditions and 27.3% in a two-chamber MEC) and the CH 4 yield increased (4.7% in the conventional conditions and 8.3% in a two-chamber MEC).…”
Section: Microscopy Of Anaerobic Activated Sludge During Anaerobic Di...supporting
confidence: 85%
“…There was a significant increase in the yield of biogas with treatment, possibly due to the specific effect of the electric current on complexly degradable quail manure. These findings are supported by previous studies conducted on substrates such as agroindustrial wastewater [28], municipal sewage sludge [29,30], and liquid waste from the wine industry [25,31]. On the sixth day of treatment, the CO 2 yield increased (24.0% in the conventional conditions and 27.3% in a two-chamber MEC) and the CH 4 yield increased (4.7% in the conventional conditions and 8.3% in a two-chamber MEC).…”
Section: Microscopy Of Anaerobic Activated Sludge During Anaerobic Di...supporting
confidence: 85%
“…To reach the specification of natural gas, the CH4 content in biogas should be upgraded at least to 95%, at which point it is called biomethane or bionatural gas [11,12]. The biomethane can be used directly as vehicle fuel or injected into the natural gas grid, thereby broadening the range of applications and increasing the value of biogas [13]. For this purpose, biogas upgrading-increasing its CH4 content by removing CO2 or converting CO2 into CH4 is necessary [14].…”
Section: Anaerobic Digestion and The Needs Of Biogas Upgradingmentioning
confidence: 99%
“…In recent years, studies have found that microbial electrolysis cell (MEC) could improve methane yield by modulating microbiota structure and promoting electron transfer (Hui et al,2021;Yanuka-Golub et al,2019;Yu et al,2020). Gao et al used MEC to treat quinoline wastewater, they found that MEC could promote the synergistic effect of quinoline-degrading bacteria and electroactive bacteria, thus achieving simultaneous quinoline wastewater treatment and methane production (Gao et al,2020).…”
Section: Introductionmentioning
confidence: 99%